MUHAMMADIYAH SEBAGAI GERAKAN ISLAM YANG BERWATAK TADJID DAN TAJRID - Sukma, Dessy Tya Melati; karina, karina; Sormin, Darliana; Lubis, Jumaita Nopriani; Wahyuni, Sri (Tarim : Jurnal Islamic Eduation, 2023)
This study discusses Muhammadiyah as an Islamic movement with tajdid and tajrid characters. This type of research is library research. This research makes Library materials as its main data source. Itaims to explore the nature of tadjid and tajrid in the Muhammadiyah movement as the main principle of da'wah and the development of krian. Muhammadiyah as an Islamic movement has a character and characteristics that are different from other Islamic organizations, this is a strategy in the process of understanding Islam comprehensively so that it can present Islam rahmatan lil alamin is not just a slogan or concept but more applicable in accordance with the concept of baldatun toyyibatun wa rabbun ghofur. The concept of Tajdid and tajrid will always accompany in every movement for the development of mhammadiyya da'wah. With this concept, Muhammadiyah is able to balance the strategy of da'wah and organizational development in line with the changing times. On the other hand, from matters of worship and muamalah will be able to run in balance, including in the development of business charity and the formation of cadres who have Islamic personalities.